The Role of Task-Based Collaborative Learning for Employability Among Technical Students of Madhya Pradesh - Kailas, Mayuri; Bhatt, Vinod (Journal of Engineering Education Transformations, 2025)
In recent years, teachers have become more interested in the use of Task-Based approaches in both foreign language and second language training. Additionally, the changing workforce demands creates new expectations for global citizens and future professionals who can operate in a team atmosphere and approach challenging issues. The purpose of this paper is to examine the contribution of Task-Based collaborative learning for the acquisition of employability skills among technical graduates. A quantitative method is used to analyze the study. For that, a questionnaire-based survey is conducted among 480 technical students across the state Madhya Pradesh, India. The questionnaire is likert-scale based that shows the opinion of respondents on various aspects.The data for this study was collected through a convenience sampling method. SPSS software is used to assess the data set. The statistical techniques such as Regression model, Pearson’s chi-squared test and Cronbach’s alpha test is performed for the comparison of variables, and to determine the internal consistency of variables, respectively. From the statistical analysis, it is evident that the p-value lies below 0.05 which shows the positive impact of Task-Based Collaborative learning in developing employability skills. Despite the limited research, the findings demonstrate that the Task-Based Language Teaching methodology through Collaborative Learning has greater effect on students’ overall development and also it is a better approach than the conventional method.